Effects of high temperature and marine heat waves on seagrasses: Is warming affecting the nutritional value of Posidonia oceanica?. (February 2023) - Stipcich, Patrizia; Beca-Carretero, Pedro; Álvarez-Salgado, Xosé Antón; Apostolaki, Eugenia T.; Chartosia, Niki; Efthymiadis, Pavlos Theofilos; Jimenez, Carlos E.; La Manna, Gabriella; Pansini, Arianna; Principato, Elena; Resaikos, Vasilis; Stengel, Dagmar B.; et al.
Abstract: Primary producers nutritional content affects the entire food web. Here, changes in nutritional value associated with temperature rise and the occurrence of marine heat waves (MHWs) were explored in the endemic Mediterranean seagrass Posidonia oceanica . The variability of fatty acids (FAs) composition and carbon (C) and nitrogen (N) content were examined during summer 2021 from five Mediterranean sites located at the same latitude but under different thermal environments. The results highlighted a decrease in unsaturated FAs and C/N ratio and an increase of monounsaturated FA (MUFA) and N content when a MHW occurred. By contrast, the leaf biochemical composition seems to be adapted to local water temperature since only few significant changes in MUFA were found and N and C/N had an opposite pattern compared to when a MHW occurs. The projected increase in temperature and frequency of MHW suggest future changes in the nutritional value and palatability of leaves. Highlights: Primary producer nutritional content may affect the functionality of the food web. Changes in nutritional value related to temperature in P.oceanica were explored. Marine heat waves increased MUFA and N content and decreased PUFA and C/N ratio. Higher local temperature stimulates higher MUFA values and C/N content, but lower N. The projected change in climate suggests a change in the nutritional value of P. oceanica .